Reflective Practice: A Method to Improve Teachers’ Well-Being. A Longitudinal Training in Early Childhood Education and Care Centers - Cigala, Ada; Venturelli, Elena; Bassetti, Martina (Frontiers in Psychology, 2019)
Abstract Various studies focused on educational contexts (0-6 years) point out that early childhood multi-age classrooms further better learning strategies and socio-emotional competences of children, compared to single-grade classrooms. However, these studies have also shed light on the significant role of teachers. The multi-age classroom in particular is an opportunity for child development, provided that teachers consider problem-solving, flexibility and co-construction as effective education strategies. Starting from these reflections, this study aimed to verify the efficacy of longitudinal training for the purpose of advancing the perceived well-being of early childhood teachers of multi-age groupings (18-54 months). Eight teachers and one pedagogical coordinator of an Italian Early Childhood Education and Care centre took part in the study. All the participants were females. The critical aspect identified by the teachers was multi-age classroom, which were perceived as very difficult and ineffective for themselves and for the children. The training lasted 10 months and implied a methodology focused on observations of some activities and reflective practice in the group that concerned both teachers and the pedagogical coordinator. The training involved the drafting of two types of written protocols: the observational reports of the specific activities observed (20), and the descriptive reports of reflective sessions (6). The content analysis of the reports revealed various and interesting themes regarding the teachers’ perceived well-being, in term of thoughts, behaviours and feelings. The qualitative and longitudinal analysis of the themes that emerged in these protocols highlighted different processes of change in the teachers’ perception, in particular with respect to three specific dimensions of well-being: sense of belonging, self-efficacy and agency. At the end of the training the teachers experienced a greater sense of belonging to the group of colleagues, a greater sense of self-efficacy and an idea of themselves as active and meaningful participants. These results supported different reflections regarding the modalities through which to enhance the perceived well-being of teachers.